An estimate of the rate of convergence in the central limit theorem by means of pseudomoments - Paulauskas, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. Паулаускас. Одна оценка скорости сходимости с использованием псевдомоментовV. Paulauskas. Konvergavimo greičio įvertinimas, panaudojant pseudomomentus